PENGARUH MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN DI PERUSAHAAN UMUM PERURI - Firman Dwi Aprianto; Solehudin Solehudin; Nunung Nurhasanah (Universitas Bina Taruna Gorontalo, 2024)
This research aims to investigate the presence of achievement motivation in the Settlement Khazsanah section of the Public Money Printing Company of the Republic of Indonesia (PERURI), as well as the performance of employees in this section. The research method used is a quantitative approach. The study was conducted with 30 Settlement Khazsanah employees. Data was collected using questionnaires.The results of the research indicate that there is a significant influence of achievement motivation on employee performance in the Settlement Khazsanah section at PERURI. This is evidenced by the calculated t-value (7.363) being greater than the t-table value (2.042), leading to the acceptance of the alternative hypothesis (Ha). Additionally, an r-value of 0.812 was obtained, indicating a very strong positive relationship between achievement motivation and employee performance. Achievement motivation contributes 65.9% to employee performance in the Settlement Khazsanah section at PERURI, with the remaining 34.1% influenced by other factors.